PHENOTYPE CHARACTERISTICS OF CROSSING PURPLE CORN AND SWEET YELLOW CORN (ZEA MAYS L.) IN GENERATION F4 - Maemunah, Maemunah; Samudin, Sakka; Mustakim, Mustakim; Akbar, Ali; Jeki, Jeki; Mas'ud, Hidayati (AGROLAND The Agricultural Sciences Journal (e-Journal), 2024)
Phenotypic characters in crossed plants is very important to find out the success of a cross and the differences in characters between one type and another. The purpose of this study was to identify and determine the best phenotypic characters resulting from crosses of maize plants in the F4 generation. This research was carried out on agricultural land in Oloboju Village (Bulu Pontu Jaya SP2), at an altitude of 176 meters above sea level, with a latitude of 1ᵒ00'21" South Latitude and 119ᵒ56'50.49" North Latitude. Sigi Biromaru District, Sigi Regency. The study started from February to July 2020. This study was structured using a randomized block design with five maize cultivars from F3 crosses as treatments, namely: purple corn cultivar, dominant yellow: purple, white dominant purple, purple dominant white, and purple dominant yellow which was repeated five times to obtain 25 experimental plots. The observed variables were: plant height, number of leaves, stem diameter, age at which male flowers were released, age at which female flowers were released, age at harvest, cob length, cob diameter, number of cob seeds, percentage of color, and weight of 100 seeds. The research data were analyzed using ovarian analysis, which was followed by the HSD test at the 1% level. The results showed that purple corn cultivars had the best phenotypic characteristics, namely, plant height reached 226.55 cm, cob diameter reached 40.95 mm, cob length reached 15.05 cm, color percentage reached 70.39%, number of cob seeds reached 411 .70 seeds and has a slightly fluffier texture and a slightly less sweet taste until it is quite sweet.